2019
DOI: 10.1007/s00521-019-04573-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrated computational intelligent paradigm for nonlinear electric circuit models using neural networks, genetic algorithms and sequential quadratic programming

Abstract: In this paper, a novel application of biologically inspired computing paradigm is presented for solving initial value problem (IVP) of electric circuits based on nonlinear RL model by exploiting the competency of accurate modeling with feed forward artificial neural network (FF-ANN), global search efficacy of Genetic algorithms (GA), and rapid local search with sequential quadratic programming (SQP). The fitness function for IVP of associated nonlinear RL circuit is developed by exploiting the approximation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 96 publications
(33 citation statements)
references
References 63 publications
(69 reference statements)
0
33
0
Order By: Relevance
“…The AI based numerical approaches have been used broadly for solution of differential equations arising in diffrenet applications [26][27][28][29][30][31]. A few recent studies of paramount significance reported include Van-der-Pol oscillatory nonlinear systems [32][33], solution of mathematical model in nonlinear optics [34], models of electrically conducting solids [35][36], analysis of nonlinear reactive transport model [37], fuel ignition model in combustion theory [38], Jeffery Hamel flow models [39][40], thin film flow models [41][42], mathematical models involving Carbon nanotubes [43][44], astrophysics [45][46], nonlinear circuit theory models [47][48], dusty plasma [49][50], atomic physics [51][52], heartbeat dynamic models [53], HIV infection spread models [54][55], piezoelectric transducer modeling [56], energy [57][58], wind power [59][60], and financial models [61][62]. Beside these stiff nonlinear fractional dynamic modeling with Riccati fractional differential equations (FrDEs) [63][64] and Bagley-Torvik FrDEs [65] The organizational plan of this study comprises of the following: In the second section, necessary infor...…”
Section: Introductionmentioning
confidence: 99%
“…The AI based numerical approaches have been used broadly for solution of differential equations arising in diffrenet applications [26][27][28][29][30][31]. A few recent studies of paramount significance reported include Van-der-Pol oscillatory nonlinear systems [32][33], solution of mathematical model in nonlinear optics [34], models of electrically conducting solids [35][36], analysis of nonlinear reactive transport model [37], fuel ignition model in combustion theory [38], Jeffery Hamel flow models [39][40], thin film flow models [41][42], mathematical models involving Carbon nanotubes [43][44], astrophysics [45][46], nonlinear circuit theory models [47][48], dusty plasma [49][50], atomic physics [51][52], heartbeat dynamic models [53], HIV infection spread models [54][55], piezoelectric transducer modeling [56], energy [57][58], wind power [59][60], and financial models [61][62]. Beside these stiff nonlinear fractional dynamic modeling with Riccati fractional differential equations (FrDEs) [63][64] and Bagley-Torvik FrDEs [65] The organizational plan of this study comprises of the following: In the second section, necessary infor...…”
Section: Introductionmentioning
confidence: 99%
“…It can be applied to optimize both constrained and unconstrained types of problems. Recently, GA is applied in many famous applications of heart diagnosis system [42], nonlinear electric circuit models [43], nonlinear astrophysics based singular system [44], Painlevé equation-II based nonlinear optic models [45], prediction model of air blast [46], Thomas Fermi model [47], and monorail vehicle system [48]. These potential applications of GA inspired the authors to solve the singular pantograph differential model to attain the decision variables of MWNNs.…”
Section: B Optimization Process: Gaipamentioning
confidence: 99%
“…The strength of artificial intelligent (AI) based computing solvers has been exploited by the research community on large scale to obtain the approximated solutions of many problems arises in broad fields of applied science and technology. Some potential, recent reported studies having paramount significance including Van-der-Pol oscillatory systems, optics, electrically conducting solids, reactive transport system, nanofluidics, nanotechnology, fluid dynamics, astrophysics, circuit theory, plasma, atomic physics, bioinformatics, energy, power and functional mathematics see [24][25][26][27][28][29][30][31][32][33][34] and references cited therein. The said information is the motivational affinities to investigate in AI base numerical computing solver for the COVID-19 model.…”
Section: Problem Statement With Significancementioning
confidence: 99%